Who is Learning about Religion? Factors that Predict First-Year Student's Curricular Decisions. Issue 2 (3rd April 2021) - Patterson, Joshua R.; Foster, Robert L.
Abstract: Recent rises in anti-Semitism and other types of religious bullying on college campuses have highlighted the importance of curricular interventions. Despite this salience, little is known about students' decisions to enroll in courses that address religious difference. This paper used logistic regression to explore the influence of institutional characteristics, student demographics, and student identity and worldview on course decisions in the IDEALS data set. A number of variables emerged as significant with the largest coefficients relating to institutional characteristics. This paper offers empirical basis for expanded curricular engagement with religious difference and advances research on student course decisions generally.